Zero gravity induced by parabolic flight enhances automatic capture and weakens voluntary maintenance of visuospatial attention - Adriana Salatino (Nature Portfolio, 2021)
Abstract Orienting attention in the space around us is a fundamental prerequisite for willed actions. On Earth, at 1 g, orienting attention requires the integration of vestibular signals and vision, although the specific vestibular contribution to voluntary and automatic components of visuospatial attention remains largely unknown. Here, we show that unweighting of the otolith organ in zero gravity during parabolic flight, selectively enhances stimulus-driven capture of automatic visuospatial attention, while weakening voluntary maintenance of covert attention. These findings, besides advancing our comprehension of the basic influence of the vestibular function on voluntary and automatic components of visuospatial attention, may have operational implications for the identification of effective countermeasures to be applied in forthcoming human deep space exploration and habitation, and on Earth, for patients’ rehabilitation.